ENT530 : Loves florist / Norazura Che Ya'acob, Zuraida Jolkopli and Nor Shahida Zakaria - Che Ya'acob, Norazura; Jolkopli, Zuraida; Zakaria, Nor Shahida (2017)
Loves Florist is a business that carries out the production of fresh floral decorations for various occasions and receive reservations from private companies and individuals. This is a partnership business. The three partners combine skills, knowledge and financial to set up the business. Our nature of business focuses on floral decoration and located at Lot 6, Tingkat Bawah, Kompleks PKNS Bangi, 43650 Bandar Baru Bangi, Selangor.